Cyclic ultracapacitor for fast-charging and scalable energy storage system. (15th December 2015) - Yeon, Sun-Hwa; Kim, Dong-Ha; Kim, Daewi; Park, Se-Kook; Yoon, Hana; Yoo, Jungjoon; Shin, Kyoung-Hee; Jin, Chang-Soo; Lee, Yun Jung; Lee, Sang-Young
Abstract: ESSs (Energy storage systems) for large-scale grid systems and next generation secondary battery systems require an ideal device that satisfies diverse properties such as a high energy density, high power density, low cost, and safe and reliable performance. In this study, we present a CUCap (cyclic ultracapacitor), which is comprised of two reservoirs and one flat flow capacitor cell with a cyclic continuous flow mode and independently tunable power rating and energy capacity. CUCap provides fast-charging and high capacity technology with a simple and practical design for high density and large-scale energy storage systems. The best performance appeared in slurry ratio (electrode to electrolyte) 1 to 7 with the total reservoir volume of 150 mL and the flow rate 300 ml/min, resulting in volumetric energy density, specific capacitance, and discharge time of 7.7 Wh L −1, 14.2 F ml −1, 100 min, respectively. Moreover, the slurry electrode of the CUCap cell had a maximum current density around 260 mA cm −2 which could possibly result in a fast-charging CUCap system. Highlights: We present a simple and non-intermittent flow capacitor, a cyclic ultracapacitor. Cyclic ultracapacitor is comprised of two reservoirs and flat flow capacitor cell with a cyclic continuous flow mode The best performance results in volumetric energy density of 7.7 Wh L −1 . Key issue of the system is increasing the energy density of the slurry electrode.